2022
DOI: 10.3390/jcm11030542
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index Specifiers in Anorexia Nervosa: Anything below the “Extreme”?

Abstract: The validity of body mass index (BMI) specifiers for anorexia nervosa (AN) has been questioned, but their applicability to inpatients with extremely low BMIs and their prognostic validity are currently unknown. Therefore, we designed this study: (a) to test current BMI specifiers in severe inpatients; (b) to explore a “very extreme” specifier (VE-AN; BMI ≤ 13.5); and (c) to verify inpatients’ hospitalization outcome according to BMI severity. We enrolled 168 inpatients with AN completing the following: Eating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
(59 reference statements)
1
13
0
Order By: Relevance
“…Also, we expected to find a positive association between BMI and all variables (i.e., the greater the BMI the greater the depressive symptoms) as reported in literature [ 49 ]. It is also noted that as BMI decreases in AN, body dissatisfaction values decrease as measured by the Body Shape Questionnaire and Eating Disorder Examination-Questionnaire [ 50 ]. The hypothesis on age was more exploratory but we expected to find a positive association instead (i.e., the greater the age the more marked the other variables).…”
Section: Introductionmentioning
confidence: 99%
“…Also, we expected to find a positive association between BMI and all variables (i.e., the greater the BMI the greater the depressive symptoms) as reported in literature [ 49 ]. It is also noted that as BMI decreases in AN, body dissatisfaction values decrease as measured by the Body Shape Questionnaire and Eating Disorder Examination-Questionnaire [ 50 ]. The hypothesis on age was more exploratory but we expected to find a positive association instead (i.e., the greater the age the more marked the other variables).…”
Section: Introductionmentioning
confidence: 99%
“…(Spielberger, 1983 ) includes 20 items assessing for trait anxiety (STAI‐T), with higher scores indicating greater severity. Cronbach's alpha of .71 (Sternheim et al, 2020 ) and .96 (Toppino et al, 2022 ) have been reported in recent samples of adults with AN.…”
Section: Methodsmentioning
confidence: 93%
“…Individuals with extreme-AN hospitalized after March 2020 showed higher levels of psychopathology in many of the investigated areas in comparison to the pre-pandemic group of extreme-AN. This finding could be interpreted in the sense that having reached an extremely low BMI was not linked to either minimization or actual reduction of pathological concerns [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work demonstrated that body-related concerns are relevant in the context of ED hospitalization and closely related to treatment outcomes [ 26 ]. Furthermore, it would be useful to assess whether individuals hospitalized for extreme-AN (i.e., with a Body Mass Index (BMI) inferior to 15 kg/m 2 ) after the start of the pandemic presented a similar or different patterns of symptoms in comparison to the pre-pandemic cohort [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%